2017
DOI: 10.3389/fnbeh.2017.00135
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injuries during Development: Implications for Alcohol Abuse

Abstract: Traumatic brain injuries are strongly related to alcohol intoxication as by some estimates half or more of all brain injuries involve at least one intoxicated individual. Additionally, there is mounting evidence that traumatic brain injuries can themselves serve as independent risk factors for the development of alcohol use disorders, particularly when injury occurs during juvenile or adolescent development. Here, we will review the epidemiological and experimental evidence for this phenomenon and discuss pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 106 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Moreover, drinking after TBI is associated with poor rehabilitation outcomes, greater morbidity and a greatly increased chance of future head injuries (Corrigan, 1995; Vaaramo et al, 2014). Given that young TBI patients are less likely to have developed problem drinking prior to injury, increasing evidence suggests that the vulnerability to alcohol abuse later in life is a consequence of TBI-related pathology (Weil et al, 2016a; Weil and Karelina, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, drinking after TBI is associated with poor rehabilitation outcomes, greater morbidity and a greatly increased chance of future head injuries (Corrigan, 1995; Vaaramo et al, 2014). Given that young TBI patients are less likely to have developed problem drinking prior to injury, increasing evidence suggests that the vulnerability to alcohol abuse later in life is a consequence of TBI-related pathology (Weil et al, 2016a; Weil and Karelina, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, although our overall sample size was relatively large, the heterogeneity of each individual disease state may have limited our power to detect the smaller effect sizes suggested by current data. Third, TBI can possibly be both a cause and a consequence of AUD (61), and the current sample did not have enough information (i.e., exact date of onset) to resolve these discrepancies. Fourth, patients with severe TBI were intentionally eliminated from the study, which may limit the generalizability of current null findings to a more mild to moderate injury group.…”
Section: Discussionmentioning
confidence: 87%
“…These changes explain the adolescents impulsive and novelty-seeking behavior traits [22]. TBI causes disruption to the developing nervous system, which increases the vulnerability to AUD and SUD [23]. TBI increases the risk of addiction by reducing the cognitive ability to perceive negative consequences and increases the perception of gains perceived by drinking and substance abuse [23].…”
Section: Discussionmentioning
confidence: 99%
“…TBI causes disruption to the developing nervous system, which increases the vulnerability to AUD and SUD [23]. TBI increases the risk of addiction by reducing the cognitive ability to perceive negative consequences and increases the perception of gains perceived by drinking and substance abuse [23]. A study by Patel et al found that cannabis abuse among youth increases the risk of intracranial injury by 1.3 times [24].…”
Section: Discussionmentioning
confidence: 99%